The national health insurance system of Indonesia and primary care physicians’ job satisfaction: a prospective qualitative study - Maharani, Chatila; Rahayu, Sri Ratna; Marx, Michael; Loukanova, Svetla (Family practice, 2022)
The implementation of the National Health Insurance System (NHIS) in Indonesia has been changing the primary care physician (PCP) work condition and their job satisfaction.This research aimed to explore the reasons behind PCPs’ satisfaction and dissatisfaction with job satisfaction’s aspect under the NHIS reform.We conducted an exploratory qualitative study within two areas in Central Java, Indonesia, using semi-structured in-depth interviews with 34 PCPs and 19 triangulation sources. We conducted both inductive and deductive analyses by the NVivo 11.Most PCPs felt dissatisfied with the following aspects of the NHIS: referral system, NHIS health services standard, NHIS programmes, performance evaluation and pay-for-performance, relationship with patient and workloads. PCPs felt constrained with the referral regulation and non-specialist diagnoses, which led to dissatisfaction with performance evaluation and the pay-for-performance implementation. Furthermore, an increase in workload and conflict with patients resulted from patients’ misunderstanding the NHIS health service procedures. However, PCPs felt satisfied with the chronic disease management programme and patients’ appreciation.This study presents the reasons behind PCPs’ satisfaction and dissatisfaction with job satisfaction’s aspect under the NHIS reform. There is a need for additional discussion among all stakeholders (Ministry of Health, Social Security Agency for Health/SSAH, primary health care and physician’s professional organizations about the non-specialist diagnoses list, performance evaluation and pay-for-performance). The government and SSAH need to improve the communication and socialization of the NHIS procedures/regulations.In 2014, Indonesia implemented a National Health Insurance System (NHIS). The reform affected the primary care physicians’ (PCPs’) work conditions and job satisfaction. This qualitative study explored the reasons behind PCPs’ satisfaction and dissatisfaction with the job satisfactions’ aspect in the NHIS. We interviewed 34 PCPs and 19 triangulation sources in Semarang City and Demak Regency (Central Java). Findings showed that most physicians felt dissatisfied with the NHIS referral system, health services standard, some NHIS programmes, performance evaluation and pay-for-performance, relationship with patients and workload. Mostly, the patients-PCPs’ conflicts were due to the misunderstanding of the NHIS health service procedures. However, the PCPs also received patients’ appreciation. For improving the reform implementation and PCPs’ job satisfaction, the physicians’ concerned, leading to dissatisfaction, must be addressed.